The European Social Fund's influence on labour supply in Poland - Kobus-Ostrowska, Dorota (Comparative Economic Research. Central and Eastern Europe, 2010)
The article analyses the use and distribution of the European Social Fund's resources among the Polish regions and identifies the target groups of their beneficiaries. Operations undertaken by offices on labor market are very important not only locally but also regionally. Available forms support creation of work places, help people without professional experience to get or develop new qualification. It is proper to continue mention effects and encourage potential assigns for participation in projects.